WHIMSICAL PROSE TYPOLOGICAL SERIES PROBLEM AND NOVELS BY V. MINIAILO - Voshchenko, Olena (Літературний процес: методологія, імена, тенденції, 2019)
The purpose of the paper is to find out the genre specificality of the V. Miniailo’s dilogy “Stars and Herrings” (1972) and “To the Bright Stars” (1975), which is considered to be the whimsical prose. The philological, the elements of the formal (the definition of genre dominant) and the comparative methods are used (comparison with the genre matrix of whimsical prose and the whimsical V. Miniailo’s novel “Eternal Ivan”, which has common topicality with the dilogy). The urgency of the article is in observing a typological series of whimsical texts and exploring innovative V. Miniailo’s creativity in the context of social realism, which is out of present-day literary researches. In the dilogy the psychological dominant is represented. The author focuses on the evolution of characters (rather than the events) and on their emotional reactions to circumstances. The tragic pathos (which is impossible for the genre matrix of whimsical prose) plays an important role in the dilogy. These features point to a socio-psychological narrative strategy (combined with a lyrical-romantic and philosophical-existential motives) as a genre dominant of the observed book. The Miniailo’s novel “Eternal Ivan” (1994) is also devoted to the events of the 1920s in the Ukrainian village, but conventionality, grotesque, parochialism and satire make it whimsical. Comparison of the text of both books of dilogy with the genre dominant of whimsical prose and the mentioned novel does not give grounds to define “Stars and Herrings” and “To the Bright Stars” as whimsical prose. Further studies of whimsical prose typological series are needed. DOI: https://doi.org/10.28925/2412-2475.2019.1316